A preliminary arrangement of Pomeranian coinage from the 11th and early 12th centuries - Bogucki, Mateusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
Researchers knew about the existence of the 11th-century Pomeranian coinage back in the 19th century. The basic source is a large hoard from the village of Łupawa (Lupow) near Słupsk, consisting mostly of imitations. The term “Łupawa imitations” has been in use in numismatics, to which – over the last 100 years – various authors have included all kinds of “barbaric” coins. The author presents a new concept for dividing the 11th-early 12th century coinage into six smaller groups. The oldest mint may have operated in Wolin which, however, collapsed in the first half of the 11th century. At the same time coinage started in Budzistowo, where it continued throughout the 11th century. In the second half of the 11th century, a second mint was established – probably in the vicinity of Słupsk, where both silver and copper coins were made. The mint, producing sub-value copper coins in the late 11th and the early 12th century, was located probably in Gdansk.